Emerging mechanisms and therapeutics in inflammatory muscle diseases - Wischnewski, Sven; Rausch, Hans-Werner; Ikenaga, Chiseko; Leipe, Jan; Lloyd, Thomas E.; Schirmer, Lucas (Trends in pharmacological sciences, 2025)
Idiopathic inflammatory myopathies (IIMs), or myositis, are rare diseases marked by immune-driven muscle damage and complications like skin lesions and interstitial lung disease (ILD). Despite advances, challenges in diagnosis and treatment persist, particularly in inclusion body myositis (IBM), where no effective therapy exists. Recent breakthroughs, including transcriptomics and insights into antibody-mediated immunity and interferon (IFN) signaling, have clarified IIM pathophysiology and spurred the development of new therapies, such as chimeric antigen receptor (CAR) T cells and Janus kinase (JAK) inhibitors. We explore the latest findings on the mechanisms underlying adult-onset IIMs, emphasizing IBM pathobiology and its unique immune and degenerative pathways, such as a selective type 2 myofiber damage and severe cell stress. Finally, we highlight the recent advances in transcriptomics, single-cell analysis, and machine learning in transforming IIM research by improving diagnostic accuracy, uncovering therapeutic targets, and supporting the development of personalized treatment strategies.
Online veröffetlicht: 11. Februar 2025, Artikelversion: 6. März 2025
Gesehen am 16.06.2025